COMMUNITY EMPOWERMENT IN THE ARCHIVES AWARENESS MOVEMENT IN WONOKROMO SURABAYA - Nurany, Fierda; Prasetijowati, Tri; Dwiyanti, Elyna (DIA: Jurnal Administrasi Publik, 2021)
The aims of this study is to explain community empowerment in an archive awareness community movement campaign in one-no-chromo villages. Archives are records of events and have value in use as various types of information sources created by institutions, organizations, and individuals. Unfortunately, Wonokromo Village is not yet properly managed as a family archive. Judging by the frequent loss of family archives such as birth certificates, family cards, and diplomas. Therefore, we hope that the community of Wonokromo Surabaya Village will be able to manage and build the archive. This study is a descriptive qualitative study using observation, interview and documentation methods. The results of this study indicate: First, what you can do to educate people about the importance of archives is to enable, empower, and protect them. Together with the empowerment of the community, we create archive lists to implement and become more interested in family archives. Second, the lack of public understanding and awareness of the importance of archive awareness is a stumbling block. So, community empowerment for the archive awareness movement in Wonokromo output is good. Governments must continue to empower communities on the importance of archival awareness, especially in disaster-prone areas.